ANALISIS KELAYAKAN TEKNIS DAN FINANSIAL INDUSTRI PENGOLAHAN YOGHURT JAGUNG (Zea Mays L.) DI KABUPATEN KETAPANG - Irfan Cholid; Martanto Martanto; A. Nova Zulfahmi; Suyaningsih Suyaningsih; Adha Panca Wardanu (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
This study aims to calculate the added value of processed corn products and to design a technically and financially feasible corn yogurt processing industry in Ketapang district. This study used a descriptive research method conducted in a survey with a population originating from sweet corn producers. The research location was conducted in Kalinilam village, southern Delta Pawan district, Ketapang district. The business unit analysis uses the Total Cost formula while the financial feasibility analysis uses the B / C ratio. The results of the technical and financial studies planning for the sweet corn yogurt industry are obtained by designing a small-scale corn yogurt processing unit with a production capacity of 400 kg/month or 2400 bottles/month. Economic analysis shows that to establish a corn yogurt processing unit requires a total investment capital of Rp. 113,723,712, -. The total production cost is Rp. 207,592,666.- with the cost of production (HPP) per bottle (100 ml) Rp. 7,208, - and the selling price of the product per bottle is Rp. 10,000 with a profit margin of 40%. The industrial feasibility test results obtained IRR value 38.316%, NPV Rp. 353,405,180, Payback Period is 1.85 years, with BEP of 9,022 units, B / C ratio of 1.43, and net R / C of 1.40. The result of this study is the feasibility of technical and financial of small-scale industrial corn yogurt processing units are feasible.